2018
DOI: 10.4236/oalib.1104996
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Credit Decision for Lending SMEs: A Case Study on National Bank of Egypt

Abstract: Small and Medium Enterprises (SMEs) play a vital role in the global economy. It had a major part in creating jobs and as a source of social stability, either there is major contribution for SMEs in Egypt as it faces great economy challenges that need cooperation from all parties. However, access to finance is still one of the greatest obstacles facing SMEs all over the world and prevents them from developing. This research is important to fill the research gap which appears in the limited researches that prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…While studies carried out by Omonigho (2017) and Iloh (2015) found a positive effect of bank credit on SME growth; studies carried out by Owolabi & Nasiru (2017) and Richard (2016) resulted in a negative relationship between bank credit to SME growth. The result from Benson (2017 andOkey (2016) concluded that there was an insignificant relationship between bank credit and SME growth. Iloh and Chioke (2015) asserted that the role of deposit money bank credits is vital to the development and growth of SMEs.…”
Section: The Impact Of Deposit Bank Credit On Sme Growthmentioning
confidence: 99%
“…While studies carried out by Omonigho (2017) and Iloh (2015) found a positive effect of bank credit on SME growth; studies carried out by Owolabi & Nasiru (2017) and Richard (2016) resulted in a negative relationship between bank credit to SME growth. The result from Benson (2017 andOkey (2016) concluded that there was an insignificant relationship between bank credit and SME growth. Iloh and Chioke (2015) asserted that the role of deposit money bank credits is vital to the development and growth of SMEs.…”
Section: The Impact Of Deposit Bank Credit On Sme Growthmentioning
confidence: 99%
“…The distribution of the loans is selective and structured. There are some aspects that banks usually consider when granting loans, such as the owner/manager character, capacity of the business, capital size, credit report, credibility, and the enterprise relationship between the bank and the borrower (Boushnak et al, 2018;Naima, Rahima, & Redouan, 2017). Despite the selective and careful consideration in granting loans, there is still a risk when a borrower defaults on a bank loan, which is called the credit risk (Heffernan, 2005).…”
Section: Credit Risk: Non-performing Loanmentioning
confidence: 99%
“…Kwaning, Nyantakyi and Kyereh (2015) confirmed that credit expansion by financiers to borrowers will depend on audited financial statements because presentation of this statements increases reliability of debtor's hence lenders credit risk declines. Boushnak et al (2018) carried out a study on reasons that influences lending to SMEs by Egypt's National Bank. The result of the study indicated that credible financial statement positively and significantly influences securing of loan from banks.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Financial institutions emphasize on several requirements that SMEs cannot fulfill when making credit decisions. The goal of financial institutions is to maximize the profit as a result they will minimize credit risk and increase returns on credit facilities by trading with borrowers who can pay high cost of credit and have low credit risk (Boushnak, Rageb, Ragab & Sakr, 2018). Financiers always utilise certain criteria when assessing loan requests before a warding credit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation